Identifikasi Salt and Pepper Noise pada Citra dengan Metode Median Filter - Berutu, Steven Gerald Parsaoran; Ari Mogi, I Komang (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
Noise is a common issue in image processing that can degrade the quality and clarity of images. In this research, we propose a method for identifying the levels of salt and pepper noise in images using  the  median  filter  technique.  The  median  filter  is  a  non-linear  filtering  approach  that effectively reduces noise by replacing the pixel values with the median value of neighboring pixels. In our approach, we apply the median filter to the image and observe the changes in the pixel values. By analyzing the differences between the original image and the filtered image, we can determine the extent of salt and pepper noise present in the image. The proposed method offers a reliable and efficient way to quantify the level of salt and pepper noise. Experimental results on various images demonstrate the effectiveness of the proposed method in accurately identifying and  quantifying  salt  and  pepper  noise  levels.  The  method  provides  valuable  insights  into  the amount of noise present in images, enabling better understanding and further processing of the image data.